2011
DOI: 10.1002/acr.20425
|View full text |Cite
|
Sign up to set email alerts
|

Use of B‐type natriuretic peptide as a screening tool for left ventricular diastolic dysfunction in rheumatoid arthritis patients without clinical cardiovascular disease

Abstract: Objective. Patients with rheumatoid arthritis (RA) are at an increased risk for heart failure and left ventricular diastolic dysfunction (LVDD). B-type natriuretic peptide (BNP) may be useful to screen for LVDD in the general population. We compared the effectiveness of BNP as a screening tool for LVDD in RA and non-RA subjects without cardiovascular disease (CVD). Methods. Study subjects were recruited from population-based samples with and without RA, excluding subjects with CVD. LVDD was assessed by 2-dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 34 publications
(40 reference statements)
2
26
0
8
Order By: Relevance
“…The RA reservoir function implies the ability of the right atrium to fill during ventricular systole, the RA conduit function corresponds to the passive RV filling in the early diastole and diastasis phases, and the RA contractile or booster pump function corresponds to the active atrial emptying at end‐diastole. It has further been reported that the right atrium performs an important function in terms of mechanical pumping, electrical regulation of heart and endocrine regulation . Impaired left atrial function or left atrial enlargement is generally considered to be proven prognostic parameters for patients with chronic left‐sided heart failure, but it remains unclear whether the same applies to the right atrium of PH patients.…”
Section: Discussionmentioning
confidence: 99%
“…The RA reservoir function implies the ability of the right atrium to fill during ventricular systole, the RA conduit function corresponds to the passive RV filling in the early diastole and diastasis phases, and the RA contractile or booster pump function corresponds to the active atrial emptying at end‐diastole. It has further been reported that the right atrium performs an important function in terms of mechanical pumping, electrical regulation of heart and endocrine regulation . Impaired left atrial function or left atrial enlargement is generally considered to be proven prognostic parameters for patients with chronic left‐sided heart failure, but it remains unclear whether the same applies to the right atrium of PH patients.…”
Section: Discussionmentioning
confidence: 99%
“…While it has been demonstrated that patients with RA have a higher prevalence of LV diastolic dysfunction as measured by echocardiography compared with age- and gender-matched subjects without RA,23–32 the mechanism underlying this observation remains unclear 18. Plasma markers such as BNP have been shown to be less effective for CVD screening in RA 5. These reports indicate a need for better strategies for evaluating patients with RA for subclinical CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with RA who develop clinical HF often have impaired left ventricular (LV) diastolic function with preserved LV ejection fraction (EF), and may present with relatively fewer signs and symptoms than patients with HF without RA 4 5. However, screening patients with RA for CVD remains controversial, and the best method for evaluation of subclinical disease remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with RA with abnormal BNP are more likely to have LVDD compared with those with normal BNP, but the specificity compared with non-RA patients (89% vs 94%, P = .02) and the positive predictive value (25%) of elevated BNP in patients with RA is low (25%) and is, therefore, not a good screening tool. 77 The duration of RA and CRP levels is independently associated with N-terminal proBNP. 78 …”
Section: Diagnostic Issuesmentioning
confidence: 98%